Synthesis of bioactive glass-ceramics: Effect of the incubation duration on mechanical properties using PBS solution - Zhi Wei Loh, Zhi Wei Loh; Mohd Zaid, Mohd Hafiz; Awang Kechik, Mohd Mustafa; Yap Wing Fen, Yap Wing Fen; Wei Mun Cheong, Wei Mun Cheong; Mayzan, Mohd Zul Hilmi (Elsevier, 2024)
Owing to its wear resistance and mechanical performance, glass-ceramics are often favoured in dental applications. However, prolonged immersion can cause material degradation and reduced strength. Typically, adding fluoride is believed to improve their properties. Hence, this work prepared fluoride-free and fluoride glassceramics via the melt-quenching technique. The samples were assessed after soaking PBS solution for 14 days. The fluoride sample exhibited a higher hardness of HV = 653 ± 2.80 and toughness of 3.37 ± 0.01 MPa⋅m1/2. This experimental results were compared to the human dentine (HV = 61.2), human enamel (HV = 510) and commercial dental glass-ceramics (HV = 408–663). The fluoride samples showed higher bioactivity, evident from the crystal formation in micrographs. Therefore, the prepared samples exhibit a promising potential as new materials for dental crown applications.